Propolis flavonoids liposome ameliorate doxorubicin-induced cardiotoxicity in rats - Ali M. Ghazi; Sijad M. Latif (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The clinical applications of doxorubicin (DOX), a potent anthracycline antineoplastic drug, is often restricted by its deleterious cardiotoxic effects. Thus, for improving usage of DOX, the aim of this study was to assess the cardio-protective effects of nanopropolis in a rat model of DOX-induced acute cardiotoxicity. Through maceration method for 7 days in ethanol then 7 days in absolute ethyl acetate, flavonoidal propolis extract was obtained. twenty albino Rats were divided in to four equal groups: Control rats that received BPS for 10 days, DOX-treated rats that recived a single I.P injection of DOX (25 mg/kg BW) on day 7 from beginning of experiment. Rats received liposome orally for 10 consecutive days and single dose of doxorubicin (25 mg/kg BW IP) on day 7 from beginning ofexperiment. Rats groups received propolis liposome formulas orally for 10 consecutive days and single dose of doxorubicin (25 mg/kg BW IP) on day 7 from beginning of experiment. Sera were collected for screening of cardiac injury markers.The administration of DOX in single dose showed high cardiac biomarkers CK-MB, Troponin I, and LDH than in the negative group. Treatment with propolisnanoformulas shown ameliorated the DOX‑induced cardiac tissue damage by decline the serum levels of CK-MB, Troponin I, and Lactate dehydrogenase.The experiment parts endorsed conclusion that nanopropolis may exhibit remarkable protective effect in DOX‑induced cardiac toxicity through improve a number of cardiac biomarkers linked with cardiac toxicity, and may be represent a potential agents for attenuation and prevention of the serious complications accompanied with DOX in clinical practice.